PENGARUH JARAK TANAM DAN PEMBERIAN KOMPOS JERAMI PADI TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG SABRANG (Eleutherine americana Merr.) - Lili Tri Anggraini; Haryati Haryati; T. Irmansyah T. Irmansyah (Universitas Sumatera Utara, 2014)
Using of traditional medicine is growing rapidly at this time. Eleutherine americana Merr. is one ofkind plants that potentially can be traditional medicine. This research is proposed to find out theproper plant spacing and addition of rice straw compost of Eleutherine americana. This researchwas conducted at Jalan Pasar 1 Tanjung Sari, Medan with altitude ± 25 m above sea level from Mayto September 2013, using factorial randomized block design with two factors. The factors werevarious plant spacing (20x15, 15x10, 10x15 cm) and addition of rice straw compost (0; 0,5; 1kg/plot or 0, 10, 20 ton/ha) used three replications. Data were analyzed with ANOVA and continuedwith Duncan Multiple Range Test (DMRT). Parameters were observed sprouting age (day), heightof plant (cm), number of bulb per sample and fresh bulb weight per sample (gram). The resultsshowed that the plant spacing effected significantly on sproutig age, height of plant except 9-12weeks after planting, and the number of bulb per sample. Addition of rice straw compost notsignificantly on any parameters. The interaction of two factors effected significantly on height ofplant 4 and 5 weeks after planting.Keywords : Plant spacing, rice straw compost, Eleutherine americana Merr.